Type studies on cyphelloid species (Agaricomycetes, Basidiomycota) described by Rick kept at Herbarium PACA - Trierveiler-Pereira, Larissa; Thorn, R. Greg; Gugliotta, Adriana De Melo (Phytotaxa, 2019)
Type specimens of cyphelloid fungi described by Johannes Rick kept at Herbarium PACA (São Leopoldo, Brazil) were studied, described, illustrated and their species names were updated when necessary. Two invalid names, Cyphella grisea Rick and Solenia minima Rick, are reduced to synonyms of existing names, Lachnella subfalcispora D.A. Reid and Henningsomyces minimus (Cooke & W. Phillips) Kuntze, respectively. Cyphella congregatissima Rick, Glabrocyphella rubescens Rick, Solenia pezizoidea Rick and Theleporus griseus Rick are combined to Seticyphella Agerer, Henningsomyces Kuntze, Maireina W.B. Cooke and Resupinatus Nees, respectively, with the last requiring a new name, Resupinatus rickii. Descriptions, color photographs of basidiomes, and line-drawing illustrations of microstructures from the examined material are given.